Implications of p75NTR for dentate gyrus morphology and hippocampus-related behavior revisited - Dokter, Martin; Busch, R.; Poser, R.; Vogt, M. A.; Bohlen und Halbach, Viola von; Gass, Peter; Unsicker, Klaus; Bohlen und Halbach, Oliver von (Brain structure & function, 2015)
The pan-neurotrophin receptor p75NTR is expressed in the adult brain in a discrete pattern. Although numerous studies have addressed its implications for hippocampal functions, the generated sets of data are surprisingly conflicting. We have therefore set out to re-investigate the impact of a deletion of the full-length p75NTR receptor on several parameters of the dentate gyrus (DG), including neurogenesis and hippocampus-related behavior by using p75NTRExIII knockout mice. Moreover, we investigated further parameters of the DG (cholinergic innervation, dendritic spines). In addition, we analyzed on the morphological level the impact of aging by comparing adult and aged p75NTRExIII mice and their age-matched littermates. Adult (4-6 months old), but not aged (20 months old), p75NTRExIII knockout mice display an enhanced volume of the DG. However, adult neurogenesis within the adult DG was unaffected in both adult and aged p75NTRExIII knockout mice. We could further demonstrate that the change in the volume of the DG was accompanied by an increased cholinergic innervation and increased spine densities of granule cells in adult, but not aged p75NTR deficient mice. These morphological changes in the adult p75NTR deficient mice were accompanied by specific alterations in their behavior, including altered behavior in the Morris water maze test, indicating impairments in spatial memory retention.
Gesehen am 30.11.2017